Urine Xpert MTB/RIF for the diagnosis of childhood tuberculosis. (February 2019) - Lopez, Anna Lena; Aldaba, Josephine G.; Morales-Dizon, Merrylle; Sarol, Jesus N.; Daag, Jedas Veronica; Ama, Ma. Cecilia; Sylim, Patrick; Salonga, Aida; Nielsen-Saines, Karin
Highlights: Obtaining specimens for diagnosis of childhood tuberculosis (TB) is challenging. Urine is readily accessible to use for childhood TB diagnosis with Xpert MTB/RIF. Among 182 presumptive childhood TB cases, 55 (30%) were diagnosed with TB disease. All urine samples were Xpert negative, even among bacteriologically diagnosed TB cases. Urine Xpert MTB/RIF was not helpful in the diagnosis of TB in children who are ambulatory. Abstract: Introduction: Xpert MTB/RIF is recommended for the simultaneous detection of tuberculosis (TB) and rifampicin resistance directly from sputum specimens. Since young children cannot always expectorate, we assessed urine as a possible specimen source to diagnose TB in children using Xpert MTB/RIF. Methods: During a field study to enhance childhood TB identification, spot urine samples were prospectively collected from consecutive ambulatory children aged 0 to 14 years presenting with presumptive pulmonary TB in community health centers. Urine Xpert MTB/RIF was performed by blinded technicians in 182 samples using 2 ml of unprocessed urine. Results: The mean age of presumptive TB cases was 5.9 years (median 5.4, range 0.1 to 14.7) with more males (113, 62%) compared to females. All urine samples tested negative for Xpert MTB/RIF, regardless of whether concentration was performed or not. Out of these 182 presumptive TB cases, 50 (28%) were clinically diagnosed and 5 (3%) were bacteriologically diagnosed to have TB disease using either sputum or nasopharyngeal aspirate specimens. Conclusions: In this community-based study, urine Xpert MTB/RIF does not appear to contribute to the diagnosis of childhood TB.